Yoruba Girl Dancing: a Nigerian/British Women’s Reading of Herodias’s Daughter in Mark 6:17–28 and Matthew 14:3–12 - Obamakin, Olabisi (Horizons in biblical theology, 2025)
This article seeks to offer a Nigerian/British women’s reading of Herodias’ daughter’s dance in Mark and Matthew by reading it alongside Simi Bedford’s Yoruba Girl Dancing. In this article, the dominant Western interpretation of Herodias’s daughter’s dance being erotic is shown to have been heavily influenced by hypersexualised art reception history in the face of no biblical evidence. By combining insights from Simi Bedford’s novel (which depicted Yoruba dance on British soil to be a public statement of resistance against European colonialism), and the important role that dance played within Yoruba life and death rituals, this article, written from the perspective of a Nigerian/British woman’s, reconfigures Herodias’s daughter’s dance to be a form of resistance against the patriarchal gaze, a prophetic ritual lament of the death of John the Baptist, a means to communicate to a higher deity, and finally a means to mark the end of the John the Baptist era.